Ten-year survival of Down syndrome births. - Hayes, Catherine (My University, 1997)
Objective: To determine the survival status of children with Down syndrome (DS), and to document factors influencing survival. Design: Follow-up study of cases identified from the Dublin European Register of Congenital Anomalies and Twins (EUROCAT) Register. Follow-up was attempted for each case until death or 1992 or until the date last known to be alive. Setting: Eastern Health Board, Dublin. Subjects: In all, 389 DS children, born between 1 January 1980 and 31 December 1989 were followed up. Results: Survival rates of 88% at one year and 82% at 10 years were found. There was a non-significant improvement in survival between the cohort born in 1980-1984 and that born in 1985-1989. Congenital heart defects reduced survival to 72% and complete atrio-ventricular canal defects (CAVD) had the poorest prognosis (58% survival at 10 years). Cases with CAVD showed a trend towards improved survival when surgically treated. Maternal age mother's county of residence, sex of infant, season of birth and presence of additional non-cardiac congenital anomalies had no impact on survival. Conclusions: Four out of five DS children now survive at least 10 years. Adequate educational and health service provision needs to be made for them, especially those with congenital heart defects. The need for studies which compare survival and quality of life in DS children with CAVD who undergo cardiac surgery versus those who do not, taking account of various selection factors, is identified.
PUBLISHED
Keywords: Down syndrome; Survival; Congenital heart disease; CAVD; Cardiac surgery